Imagining the future through revisiting the past: the value of history in thinking about R(R)I’s possible future(s) - Danielle Shanley (Journal of Responsible Innovation, 2021)
Despite reflexivity being held up as a core pillar of Responsible Research and Innovation (R(R)I), actors in the field have yet to consider the importance of R(R)I's history. Acknowledging field has multiple histories, not only the ones that are told but also the ones that could be told, is necessary in order to meet the requirement of reflexivity. Inspired by the notion of ANTihistory, I therefore propose an alternative historiography. Based on ethnographic and archival research, I trace some of the interactions between early iterations of Science and Technology Studies (STS) and Technology Assessment (TA) which do not regularly feature as a part of R(R)I's established history, thereby drawing attention to potentially ‘forgotten' or ‘neglected' histories. I also propose the Appropriate Technology (AT) movement as an ‘alternative' forebear of R(R)I. I argue that the interpretative richness offered by empirical historical analysis provides insights for thinking about R(R)I’s possible future(s).